2019
DOI: 10.1186/s12284-019-0311-0
|View full text |Cite
|
Sign up to set email alerts
|

1k-RiCA (1K-Rice Custom Amplicon) a novel genotyping amplicon-based SNP assay for genetics and breeding applications in rice

Abstract: Background While a multitude of genotyping platforms have been developed for rice, the majority of them have not been optimized for breeding where cost, turnaround time, throughput and ease of use, relative to density and informativeness are critical parameters of their utility. With that in mind we report the development of the 1K-Rice Custom Amplicon , or 1k-RiCA, a robust custom sequencing-based amplicon panel of ~ 1000-SNPs that are uniformly distributed across the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 96 publications
0
57
0
Order By: Relevance
“…Although cost comparisons can be difficult to make between genotyping platforms due to differences in SNP call rates, informativeness, and varying prices depending on sample commitments, the C7AIR gives the global research community a uniform tool to easily compare across research programs while being of high enough density to meet the requirements for a variety of research applications. It has also served as a resource to identify informative SNPs that can be deployed in low-cost, low-density genotyping assays such as KASP assays widely used for marker-assisted selection in forward breeding, or the 1K-Rice Custom Amplicon (1k-RiCA) SNP assay (https://gsl.irri.org/services/genotyping/rica) used for genomic selection [35].…”
Section: Implementation Of the C7airmentioning
confidence: 99%
“…Although cost comparisons can be difficult to make between genotyping platforms due to differences in SNP call rates, informativeness, and varying prices depending on sample commitments, the C7AIR gives the global research community a uniform tool to easily compare across research programs while being of high enough density to meet the requirements for a variety of research applications. It has also served as a resource to identify informative SNPs that can be deployed in low-cost, low-density genotyping assays such as KASP assays widely used for marker-assisted selection in forward breeding, or the 1K-Rice Custom Amplicon (1k-RiCA) SNP assay (https://gsl.irri.org/services/genotyping/rica) used for genomic selection [35].…”
Section: Implementation Of the C7airmentioning
confidence: 99%
“…They further suggested that GS, informed by GWAS interpretations of genetic architecture and population structure, can be an effective tool to increase the efficiency of rice breeding as genotyping is becoming cost effective. Recently, a robust genotypic platform, 1K‐Rice Custom Amplicon (1k‐RiCA), is reported as an alternative cost‐effective genotypic platform for indica rice breeding programmes, which can enhance the efficiency of MAS and GS in indica rice germplasm pools (Arbelaez et al ., 2019).…”
Section: Genomic Breeding For Developing Ddsr Varietiesmentioning
confidence: 99%
“…Identifying, preserving, and using these genetic resources effectively is essential for sustainable development of aquaculture species (Guo, 2009). Genetic markers that differentiate populations can be useful to assign unknown origin individuals to populations of origin (Beacham et al, 2017), to detect domestic population influence (e.g., introgression of domesticated alleles) (Wringe et al, 2018), and to manage broodstock (Arbelaez et al, 2019). Once markers are identified, they can be used to generate robust, multi-purpose high throughput amplicon sequencing panels (Meek & Larson, 2019) or be added to SNP chips (Gutierrez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%